Decoding Verbal and Non-Verbal on Falala Chocolate’s Advertisements: - Ega Pratiwi, Ni Kadek Adelia; Eka Pratiwi, Desak Putu (Udayana University, 2026)
This study aims to analyze the verbal and nonverbal signs in Falala Chocolate’s Instagram advertisements and to understand the implicit meanings within them. The background of this study is the important role of social media advertising in shaping audience perceptions and conveying emotional and cultural messages. The analysis uses Roland Barthes’ media semiotics (1986) to explore meaning through denotation and connotation. This study applies a qualitative approach through systematic data collection, classification of signs, and interpretation of verbal and nonverbal elements. Barthes’ analysis reveals connotative meanings such as luxury, warmth, and cultural values expressed through facial expressions, gestures, and the interaction between text and visuals. Therefore, Falala Chocolate’s advertisements not only provide product information but also build emotional appeal and communicate cultural values.